2011
DOI: 10.1016/j.jbusvent.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Career choice intentions of students with family business background

Abstract: Personal and motivational patterns of intentional founders have been researched in great depth; however, antecedents to career choices of intentional successors have been conspicuously missing in entrepreneurship research. By drawing on theory of planned behavior, we investigate how intentional founders, successors, and employees differ in terms of locus of control and entrepreneurial self-efficacy as well as independence and innovation motives. We find that transitive likelihood of career intent depends on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
494
1
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(587 citation statements)
references
References 110 publications
24
494
1
18
Order By: Relevance
“…Prior research has shown that entrepreneurial intentions depend on age (Birley 2002;Matthews and Moser 1996), gender (Carter et al 2003;Verheul et al 2012), marital status (Amit et al 1995), nationality (Bosma et al 2008), the presence of self-employed parents (Laspita et al 2012;Hoffmann et al 2015), study level (Laspita et al 2012), and study field (Zellweger et al 2011). We therefore control for these factors.…”
Section: Control Variablesmentioning
confidence: 99%
“…Prior research has shown that entrepreneurial intentions depend on age (Birley 2002;Matthews and Moser 1996), gender (Carter et al 2003;Verheul et al 2012), marital status (Amit et al 1995), nationality (Bosma et al 2008), the presence of self-employed parents (Laspita et al 2012;Hoffmann et al 2015), study level (Laspita et al 2012), and study field (Zellweger et al 2011). We therefore control for these factors.…”
Section: Control Variablesmentioning
confidence: 99%
“…Vê-se o reconhecimento desse fato, por exemplo, no Global University Entrepreneurial Spirit Student Survey (GUESSS -www.guesssurvey.org), realizado desde 2003 e organizado por pesquisadores da Universidade St. Gallen, Suíça. Ele utiliza na coleta e na análise de dados, para estudantes que são fundadores intencionais e outros, uma classificação crescente da intenção empreendedora (Sieger, Fueglistaller, & Zellweger, 2011), algo que se repete em diferentes publicações feitas a partir do GUESSS (por exemplo: Laspita, Breugst, Heblich, & Patzelt, 2012;Lima et al, no prelo;Zellweger, Sieger, & Halter, 2011).…”
Section: Hipótesesunclassified
“…According to Obschonka, Silbereisen, and SchmittRodermund (2010), it was because the function of time and experience helped to achieve more positive results in the future, and success was the result of the efforts. Ultimately personal attitude persists to the perceived feasibility as the key factor of self-efficacy (Zellweger, Sieger, & Halter, 2011). In previous research, Fayolle and Gailly (2015) found that self-efficacy significantly influenced entrepreneurial behavior and was a key tool in entrepreneurship education to improve students' entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 97%
“…The entrepreneurial intention is learned in the most venture creation. By doing that, a person can have a greater perceived behavioral control and the intention to become self-employed than before (Zellweger, Sieger, & Halter, 2011).…”
Section: Introductionmentioning
confidence: 99%